Bioethical Analysis of Reproductive Rights and Replacement Pregnancy - Denisse Isabel Suaste Pazmiño (Medisur)
Biotechnological and scientific advances in the medicine field have allowed couples with difficulties to get pregnant to do so through artificial human reproduction processes. Replacement pregnancy or surrogacy is an assisted human reproduction technique, that gives women with no functional uterus, homosexual couples and single men the opportunity, to achieve the goal of being fathers and/or mothers. This article aims to analyze the bioethical dilemmas regarding reproductive rights and surrogacy. A bibliographic review was carried out in: Pubmed, Oxford Journals, ProQuest, Cochrane, Scielo, Dialnet and IBECS databases. Surrogacy presents arguments in favor of respect for the individuals' reproductive and sexual rights. The application of this technique must be carried out with an altruistic objective, by applying contractual processes in which both parties involved benefit and the States provide ethical and legal guarantees to protect the rights of women, children and reproductive rights.